2022
DOI: 10.1177/08944865221100374
|View full text |Cite
|
Sign up to set email alerts
|

When Family Business Meets Social Enterprise: An Integrative Review and Future Research Agenda

Abstract: Although family businesses and social enterprises are typically examined as distinct organizational forms, research in both domains recognizes the significant influence of family on organizational goals. Our cross-disciplinary review of 104 articles, published in 50 journals between 1996 and 2020, capitalizes on this family connection and synthesizes the varied ways family influence has been examined in extant literature. Our review considers the role of the family in shaping social missions and directing soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…This framework enables us to reinterpret the outwardoriented social legacy as a network of meanings that is transmitted to different stakeholders through leveraging historical narratives, that is, stories about the past (Suddaby et al, 2010(Suddaby et al, , 2023, around the family, and/or the family business (Coraiola et al, 2015;Foster et al, 2017). While current research has covered the particular role of family firms vis-à-vis the local community (Randolph et al, 2022;Reay et al, 2015), stakeholder groups (Cennamo et al, 2012), and the broader social context (De Massis et al, 2016), it does not explain the rhetorical mechanisms through which family firms communicate an outward-oriented social family legacy. Thus, we ask the following research question: How do family firms engage in rhetorical history to transfer their social family legacy outward?…”
Section: Introductionmentioning
confidence: 99%
“…This framework enables us to reinterpret the outwardoriented social legacy as a network of meanings that is transmitted to different stakeholders through leveraging historical narratives, that is, stories about the past (Suddaby et al, 2010(Suddaby et al, , 2023, around the family, and/or the family business (Coraiola et al, 2015;Foster et al, 2017). While current research has covered the particular role of family firms vis-à-vis the local community (Randolph et al, 2022;Reay et al, 2015), stakeholder groups (Cennamo et al, 2012), and the broader social context (De Massis et al, 2016), it does not explain the rhetorical mechanisms through which family firms communicate an outward-oriented social family legacy. Thus, we ask the following research question: How do family firms engage in rhetorical history to transfer their social family legacy outward?…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we chose this approach to minimize the subjectivity of review and analysis (Hodgkinson & Ford, 2014). We further relied on best practices for conducting systematic literature reviews in the field of family business research (for examples, see Magrelli et al, 2022; Randolph, Alexander, et al, 2022; Stasa & Machek, 2022). The overall literature search and selection process is illustrated in the flow diagram presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…H. Anderson & Lemken, 2023) as well as intensive discussions among the author team (see concept of communicative validity; Kvale, 1995). Based on best practice review articles in the family business context (e.g., Magrelli et al, 2022; Randolph, Alexander, et al, 2022; Stasa & Machek, 2022), we organized the literature according to the following elements across all articles: theoretical perspectives, definitional approaches of resilience in family business and its measurement, level of analysis, methodology, sample description and context, key findings, and future research suggestions. Initially, the first and second authors independently read all 87 articles to become familiar with the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Even if survival is often an assumed precondition for other desirable outcomes such as growth and financial performance, there is no clear consensus why a business would aim to endure over a long time in the first place, when long-term survival goals can negatively impact short-term financial performance and the chance for making a profitable exit (Josefy et al, 2017). In the case of family businesses, however, research has shown that these firms often prioritize nonfinancial goals such as long-term sustainability (Chrisman et al, 2012; Zellweger, 2007), care for multiple stakeholders (Cennamo et al, 2012), and local prosperity (Randolph et al, 2022). This makes the longevity of family businesses a matter of considerable societal interest (Astrachan & Jaskiewicz, 2008; Colli & Larsson, 2014).…”
Section: Introductionmentioning
confidence: 99%